PENGARUH SELF-REGULATED LEARNING DAN DUKUNGAN ORANG TUA TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI PROGRAM STUDI IPS SMA NEGERI DI KOTA JOMBANG - Sucipto, Sucipto (UNIVERSITAS NEGERI SURABAYA, 2014)
This research aims at knowing how broad the influence of self-regulated learning (SRL) and parents support towards students learning outcomes class social in economic subjects in State Senior High Schools in Jombang. This research used quantitative correlational approach which is done in three schools, they are SMA Negeri 1 Jombang, SMA Negeri 2 Jombang and SMA Negeri 3 Jombang in total of 463 social students as the subject. The data collection method in this research covers questionnaire, documentation, and interview. The sampling technique used random sampling technique. The data analysis technique used multiple linier regression statistical. The result of this research shows that there is significant influence between self-regulated learning (SRL) and parents support towards students achievement in economic subject social class in State Senior High Schools in Jombang